2020
DOI: 10.5761/atcs.oa.19-00184
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26b Suppresses the Development of Stanford Type A Aortic Dissection by Regulating HMGA2 and TGF-β/Smad3 Signaling Pathway

Abstract: Purpose: Stanford type A aortic dissection (TAAD) is one of the most dangerous cardiovascular diseases. MicroRNAs (miRNAs) have been considered as potential therapeutic targets for TAAD. In this present study, we aimed to investigate the functional role and regulatory mechanism of miR-26b in TAAD development. Materials and Methods: MiR-26b mRNA expression was detected by real-time polymerase chain reaction (RT-PCR) and protein levels were measured by Western blot. Verifying the direct target of miR-26b was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…54 In addition, miR-26b has been reported to impede Stanford type A aortic dissection (TAAD) development by regulating its direct target genes HMGA2 and TGFβ/Smad3 signalling pathway. 55 According to our cell experiments, we found that SMAD2/3, TGFβ RI and TGFβ RII can be upregulated by miR-26a, which can be downregulated by miR-26a inhibition. Moreover, the proangiogenic effects of SA-Exo-derived miR-26a on SHED and HUVECs can be ameliorated by using a TGFβ RI inhibitor.…”
Section: Discussionmentioning
confidence: 67%
“…54 In addition, miR-26b has been reported to impede Stanford type A aortic dissection (TAAD) development by regulating its direct target genes HMGA2 and TGFβ/Smad3 signalling pathway. 55 According to our cell experiments, we found that SMAD2/3, TGFβ RI and TGFβ RII can be upregulated by miR-26a, which can be downregulated by miR-26a inhibition. Moreover, the proangiogenic effects of SA-Exo-derived miR-26a on SHED and HUVECs can be ameliorated by using a TGFβ RI inhibitor.…”
Section: Discussionmentioning
confidence: 67%
“…miR-26b regulates the expression of HMGA2, thereby indirectly regulating VSMC proliferation and apoptosis, and activates the TGF-β/SMAD3 signalling pathway to promote VSMC proliferation. 94 miR-26b was found to be negatively correlated with the risk and severity of TAAD, and miR-26b expression was decreased in ascending aorta tissue of TAAD patients. It was confirmed as a biomarker for TAAD diagnosis, which can predict the risk of AD, assess the prognosis and serve as a basis for choosing the timing of surgery.…”
Section: Microrna-26b (Mir-26b)mentioning
confidence: 91%
“…It was confirmed that the miR‐26b/ HMGA2 axis contributes to TAAD development through the TGF‐β signalling pathway. miR‐26b regulates the expression of HMGA2 , thereby indirectly regulating VSMC proliferation and apoptosis, and activates the TGF‐β/SMAD3 signalling pathway to promote VSMC proliferation 94 . miR‐26b was found to be negatively correlated with the risk and severity of TAAD, and miR‐26b expression was decreased in ascending aorta tissue of TAAD patients.…”
Section: Mirnas In Aortic Dissectionmentioning
confidence: 98%
“…c-Ski inhibits the proliferation of aortic smooth muscle in A10 rats by suppressing SMAD3 signaling ( Li et al, 2013 ). Furthermore, miR-26b suppresses AD development by targeting regulation of the HMGA2 and TGF-β/SMAD3 signaling pathways; knockdown of miR-26b expression inhibited VSMC proliferation in a SMAD3-dependent way ( Yang et al, 2020 ). Experiments on the response to vascular injury showed that the loss of SMAD3 in mice resulted in enhanced intima hyperplasia.…”
Section: Tgfβr1 and Tgfβr2 Genesmentioning
confidence: 99%